PELAKSANAAN FUNGSI DAN PROSES PEMBENTUKAN PERATURAN DAERAH DI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SUMATERA UTARA - Muhammad Yasser; Mirza Nasution (Smart Education, 2024)
Abstract: Strengthening the function of forming regional regulations/legislative function of the DPRD in forming regional regulations has formal juridical legitimacy based on Article 18 paragraph (6) of the 1945 Constitution of the Republic of Indonesia that